When Parathyroidectomy Should Be Indicated or Postponed in Adolescents With MEN1-Related Primary Hyperparathyroidism - Marini, Francesca; Giusti, Francesca; Tonelli, Francesco; Brandi, Maria Luisa (Frontiers in Endocrinology, 2018)
Multiple Endocrine Neoplasia Type 1 (MEN1) is a rare inherited endocrine tumor syndrome principally affecting parathyroid glands, neuroendocrine tissues of the gastro-entero-pancreatic and thoracic tracts, and anterior pituitary, caused by germline inactivating mutations of the MEN1 tumor suppressor gene. Primary hyperparathyroidism (PHPT) is usually the first clinical manifestation of the syndrome, normally manifesting during the third decade of life. Cases of affected children and adolescents have been described by the age of 5. Clinical characteristics and therapeutic management of MEN1 in adolescents have been described mainly by case reports. Only two studies on MEN1 patient series under the age of 22 years have recently been published. Given the scarcity of data and the lack of a consistent number of targeted studies, there are currently no specific guidelines available for children and adolescents with MEN1; diagnostic and therapeutic management is, thus, usually the same as for adult patients. Here, we report our experience with 19 adolescent MEN1 patients, developing MEN1-associated PHPT before the age of 20. Fourteen of them, manifesting hypercalcemic PHPT before the age of 20 underwent parathyroidectomy before the age of 25 to control calcemia. Parathyroid surgery restored normal calcemia in all the operated patients. No post-surgical nephrolithiasis has been reported after a mean of 12.0 + 5.8 years of follow-up. Comparison between pre-surgical and post-surgical values of bone mineral density (BMD) in 2 patients evidenced an improvement of bone mass after parathyroid adenoma ablation. Two patients (14.28%) developed permanent post-surgical hypoparathyroidism.